2019
DOI: 10.1088/1742-6596/1305/1/012053
|View full text |Cite
|
Sign up to set email alerts
|

Dose reconstruction including dynamic six-degree of freedom motion during prostate radiotherapy

Abstract: An in-house developed program for real-time reconstruction of motion-induced dose errors, DoseTracker, was extended to handle rotational target motion in addition to the previously implemented translational motion, and applied offline for prostate VMAT treatments. For translational motion, the motion-induced errors of DoseTracker were in good agreement with ground truth dose reconstructions performed in a commercial treatment planning system. For rotational motion, no ground truth was available, but DoseTracke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 10 publications
3
12
0
Order By: Relevance
“…Dose reconstructions assuming constant rotations deviated largely from film doses, showing that such an assumption may be inadequate for dynamic treatments such as VMAT. This is in alignment with a preliminary study that also performed dose reconstruction with dynamic rotations 27 using a home‐made dose reconstruction method without experimental validation.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Dose reconstructions assuming constant rotations deviated largely from film doses, showing that such an assumption may be inadequate for dynamic treatments such as VMAT. This is in alignment with a preliminary study that also performed dose reconstruction with dynamic rotations 27 using a home‐made dose reconstruction method without experimental validation.…”
Section: Discussionsupporting
confidence: 81%
“…Still, the approach may be used to evaluate treatments with known prostate rotations under the assumption that interplay effects are negligible 25 . Dose reconstruction considering dynamic prostate rotations has been conducted in a single study that demonstrated large prostate dose distortions owing to interplay effects 27 . However, the study only included one case, it used in‐house developed dose calculations rather than a commercial TPS, and it was not experimentally validated.…”
Section: Introductionmentioning
confidence: 99%
“…While several methods for dose reconstruction are described in literature, popular approaches are based on combining the simulated or delivered beams with the prostate intrafraction motion, obtained by tracking implanted fiducial markers with kilovoltage (kV) imaging [10] , megavoltage (MV) imaging [5] or using magnetic implanted markers with the Calypso system [6] . Although these methods can provide a fair estimation of the delivered dose to the prostate, they lack soft tissue intrafraction information of surrounding OAR [2] and can therefore not be used to accurately reconstruct the delivered dose in the OARs.…”
Section: Introductionmentioning
confidence: 99%
“…Although dose-guidance was superior to geometry guidance in all the studied cases, it will be more important for more complex cases that are not easily understood from geometry alone. One example is when dose deficits caused by rotational motion [20,21] are to be compensated by translational couch corrections. Another example is when conflicting dosimetric requirements arise because several targets or OARs move relative to each other.…”
Section: Discussionmentioning
confidence: 99%